The Arachidonic Acid Metabolism Mechanism Based on UPLC-MS/MS Metabolomics in Recurrent Spontaneous Abortion Rats - Li, Meihe; Haixia, Yang; Kang, Minchao; An, Peng; Wu, Xili; Dang, Huimin; Xu, Xin (Frontiers in Endocrinology, 2021)
Recurrent spontaneous abortion (RSA) remains a critical and challenging problem in reproduction. To discover novel biomarkers for RSA, Ultra performance liquid chromatography/tandem mass spectrometry (UPLC-MS/MS) metabolomics approach was applied to detect RSA serum metabolic profiles and explore its possible pathogenesis and mechanism. The abortion rat model was established, and a metabolomics analysis was performed to evaluate the differentially expressed metabolites between the control and model groups. Immunohistochemistry (IHC), qRT-PCR, and Western blot further examined the expression of Arachidonic acid metabolism-related genes in uterus tissues. To identify Arachidonic acid metabolism-related changes in RSA, Elisa's potential mechanisms were further confirmed in serum. Ninety-one metabolites were significantly different between the two groups, as indicated by a VIP ≥ 1, fold change ≥ 1. The metabolic pathways involving Arachidonic acid metabolism pathway (P = 0.00044) are related to RSA. Verification by experimental showed that compared with the control rats, the expression of the COX-1, COX-2, PTGFR, and TBXA2R genes associated with the Arachidonic acid metabolism pathway has significantly increased the uterus and serum of RSA rats (P < 0.05). Regulation of the Arachidonic acid metabolism pathway might serve as a promising therapeutic strategy for relieving RSA women's symptoms.